2014
DOI: 10.1097/jcp.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Pro Re Nata (As Needed) Psychotropic Medication Use in Patients With Borderline Personality Disorder and Subjects With Other Personality Disorders Over 14 Years of Prospective Follow-Up

Abstract: The use of PRN (as-needed) psychotropic medication in borderline patients has not been well characterized. This study had three purposes: (i) to describe the prevalence of PRN psychotropic medication use among borderline patients and other personality-disordered comparison subjects over 14 years of prospective follow-up; (ii) to examine the rates reported by ever-recovered and never-recovered borderline patients; and (iii) to examine the reasons for taking PRN medication reported by these patients. Overall, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…After 16 years of prospective follow-up, 18.6 and 6.9% of BPD patients report taking four or more and five or more psychotropic medications, respectively [ 59 ]. In the same cohort over 14 years of follow-up, nearly one-third consistently used PRN medication despite the absence of any evidence-based protocols for prescribing PRNs for BPD [ 60 ]. The wish to be helpful and perceived “pressure to do something” for patients presenting in acute distress reporting unrelenting agitation, anxiety, and insomnia may account for the tendency to prescribe outside of evidence-based parameters.…”
Section: Introductionmentioning
confidence: 99%
“…After 16 years of prospective follow-up, 18.6 and 6.9% of BPD patients report taking four or more and five or more psychotropic medications, respectively [ 59 ]. In the same cohort over 14 years of follow-up, nearly one-third consistently used PRN medication despite the absence of any evidence-based protocols for prescribing PRNs for BPD [ 60 ]. The wish to be helpful and perceived “pressure to do something” for patients presenting in acute distress reporting unrelenting agitation, anxiety, and insomnia may account for the tendency to prescribe outside of evidence-based parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have reported high consumption of psychotropics in individuals with cluster B PDs (20-31). Nevertheless, most of these studies were cross-sectional (21,22,26,28,30), focused on borderline individuals (21-23, 25,26,28,31), were conducted in small samples (26,31), or considered only hospitalized patients (25,26,31), those participating in mental health programs (20, 22, 23, 29), or those followed by a psychiatrist (21).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of sleep disturbance (Plante et al, 2013a) and dysfunctional cognitions about sleep appear to be associated with poor improvement over time in the symptoms of borderline PD (Plante et al, 2013b). Unsurprisingly, poor sleep is therefore a common contributor to the decision to prescribe psychotropic medication for people with CEN (Martinho et al, 2014; Paton et al, 2015; Plante et al, 2009).…”
Section: Introductionmentioning
confidence: 99%